The diagnostic accuracy of clinical and blood examination for sepsis in potentially infected neonates - Ari Mulyani, Ari Mulyani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Neonatal sepsis remains a diagnostic challenge due to its nonspesific symptoms. Blood culture examination which is considered to be the gold standard, sometimes it is still a problem because takes time to get the result, expensive and not every health facility is able to perform.Objective: To evaluate the diagnostic accuracy of clinical symptoms, hematologic findings and C-Reactive Protein (CRP) in neonatal sepsis.Methods: Samples were taken from potentially infected neonates admitted to the Maternal-Perinatal Unit of Dr. Sardjito Hospital, Yogyakarta, between December 1st, 2000 to March 31st, 2001 using at least one of the criteria: prematurity (15,000/pL), premature rupture of the membrane (>24 hours), thick and cloudy amniotic fluid. Clinical symptoms, total white blood cell count, total neutrophil count, platelet count, CRP, and blood culture as gold standard were examined.Results: Among 99 neonates who were enrolled in this study, the sensitivity, specificity, positive predictive value and negative predictive value of clinical symptoms were 79.3%, 75.7%, 57.5%, and 89.9%, respectively; leukopenia/leukocytosis were 27.6%, 85.7%, 44.4%, and 74.1%, neutropenia/neutrophilia were 41.4%, 71.4%, 37.5%, and 74.6%, thrombocytopenia were 79.3%, 51.8%, 40.4%, and 85.7%, positive CRP were 58.6%, 78.6%, 53.1%, and 82.1%. Parallel test (clinical manifestation, thrombocytopenia, and CRP) increasing sensitivity up to 89.7%. Specificity, positive predictive value, negative predictive value, and likelihood ratio were 44.3%, 40%, 91.2%, and 1.6, respectively. Serial test (CRP, clinical manifestation, and thrombocytopenia) increasing the spesificity up to 88.6%. Sensitivity, positive predictive value and negative predictive value were 58.6%, 68%, and 83.8%, respectively, likelihood ratio was 5,1.Conclusion: Clinical sepsis, thrombocytopenia and CRP were sufficiently accurate as diagnostic test for sepsis in potentially infected neonate. Using parallel test increased the sensitivity, where negative finding reveals no sepsis. Serial test increased specificity. There was high probability of having sepsis, if the result was positive.Key words : Neonatal sepsis - clinical symptoms - hematologic findings - C-reactive protein